Investigation and Analysis of 49343 Case Women's Vaginal Microecology - Qiuhua Jia; Fei Yu; Yong Ding; Qi Cao; Hua Wei; Chunling Ma (Tehran University of Medical Sciences, 2022)
Background: We aimed to investigate the pathogen infection in vaginal secretions of women in Linyi area. Methods: From October 2016 to September 2018, a total of 49,343 vaginal secretion specimens from women who attended Women and Children's Health Care Hospital of Linyi District, Shandong Province, China were used to detect the cleanliness, Candida, clue cells, Trichomonas, etc. with Ultra-high power microscopy. Results: Among the 49343 patients, 6377 had vaginal cleanliness of degree Ⅰ～Ⅱ, the detection rate was 37.89%; 10455 cases of Ⅲ～Ⅳ degree, the detection rate was 62.11%; 13193 cases of simple vaginal pathogen infection, the detection rate was 26.74%. Among them, 9256 cases of vaginal Candida (VVC) had a detection rate of 18.76%; 3176 cases of Bacterial vaginosis (BV) had a detection rate of 6.44%; and 761 cases of Trichomonas infection (TV) had a detection rate 1.54%; 899 cases of mixed infection. The detection rate was 1.82% and the detection rate of each pathogen in the 18-30 year old group was the highest. The detection rates of VVC, BV, TV and MVI were 10.80%, 3.25%, 0.65%, 1.00%, repsectively. Conclusion: The incidence of VVC women with vaginitis in Linyi was the highest, and the incidence was mainly between 18 and 40 years old. The infection rate of VVC, BV and MVI pathogens was the highest in summer, and the infection rate of TV was the highest in autumn.